Complementary and Alternative Medicine for Postoperative Pain: A Systematic Review. (20th May 2020) - Bakker, Caitlin J.; Wise, Kelsey L.; Williams, Benjamin R.; Swiontkowski, Marc F.
Abstract : Background: The treatment of postoperative pain is an ongoing challenge for orthopaedic surgeons. Poorly controlled pain is associated with poorer patient outcomes, and the prescription of opioids may lead to prolonged, nonmedical use. Complementary and alternative medicine is widely adopted by the general public, and its use in chronic musculoskeletal pain conditions has been studied; however, its efficacy in a postoperative context has not yet been established. Methods: We conducted a systematic literature review of 10 databases to identify all relevant publications. We extracted variables related to pain measurement and postoperative opioid prescriptions. Results: We identified 8 relevant publications from an initial pool of 2, 517 items. Of these, 5 were randomized studies and 3 were nonrandomized studies. All 8 studies addressed postoperative pain, with 5 showing significant decreases (p < 0.05) in postoperative pain. Also, 5 studies addressed postoperative opioid use, with 2 showing significant differences (p < 0.05) in opioid consumption. Substantial heterogeneity among the studies precluded meta-analysis. No articles were found to be free of potential bias. Conclusions: Currently, there is insufficient evidence to determine the efficacy of complementary and alternative medicines for postoperative pain management or as an alternative to opioid use following orthopaedic surgery. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.